2007
DOI: 10.1037/0012-1649.43.3.719
|View full text |Cite
|
Sign up to set email alerts
|

Cross-classification and category representation in children's concepts.

Abstract: Items commonly belong to many categories. Cross-classification is the classification of a single item into more than one category. This research explored 2- to 6-year-old children's use of 2 different category systems for cross-classification: script (e.g., school-time items, birthday party items) and taxonomic (e.g., animals, clothes). The results of Experiments 1 and 2 show that by a young age, children are able to cross-classify items into both category systems. Experiment 3 found that children mentally rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 78 publications
5
61
2
3
Order By: Relevance
“…Finally, Ross & Murphy showed that both taxonomic and situation-based category labels prime retrieval of category members, and that both kinds of categories can guide inferences in inductive reasoning. Similar results have been obtained by researchers investigating the domains of biology (Shafto & Coley, 2003;Boster & Johnson, 1989;Medin et al, 2005;Proffitt, Coley, & Medin, 2000) and person categorization (Nelson & Miller, 1995;Smith, Fazio, & Cejka, 1996;Zarate & Smith, 1990), and in research with children (Nguyen & Murphy, 2003;Nguyen, 2007). Together, these results provide a compelling demonstration that people spontaneously produce, consistently agree about, and reason based on multiple systems of categories.…”
Section: Empirical Evidence For Cross-cutting Systems Of Categoriessupporting
confidence: 80%
“…Finally, Ross & Murphy showed that both taxonomic and situation-based category labels prime retrieval of category members, and that both kinds of categories can guide inferences in inductive reasoning. Similar results have been obtained by researchers investigating the domains of biology (Shafto & Coley, 2003;Boster & Johnson, 1989;Medin et al, 2005;Proffitt, Coley, & Medin, 2000) and person categorization (Nelson & Miller, 1995;Smith, Fazio, & Cejka, 1996;Zarate & Smith, 1990), and in research with children (Nguyen & Murphy, 2003;Nguyen, 2007). Together, these results provide a compelling demonstration that people spontaneously produce, consistently agree about, and reason based on multiple systems of categories.…”
Section: Empirical Evidence For Cross-cutting Systems Of Categoriessupporting
confidence: 80%
“…Recently, there has been increasing recognition that children have the ability to use different systems of categorization to think about the same items (e.g. Nguyen, 2007b;Nguyen & Murphy, 2003). For example, ice cream can be considered as belonging to both a taxonomic category (dairy products) and a script category (things at a birthday party).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the versatile use of categorization in consumer research, several of these studies support that the food domain can be organized in multiple ways (Nguyen, 2007;Nguyen & Murphy, 2003;Ross & Murphy, 1999). Particularly, taxonomic categories seem to be more common and accessible, and are more likely to be used as a kind of neutral organization (Beltran et al, 2008b;Blake et al, 2007;Ross & Murphy, 1999).…”
Section: The Strong Taxonomic Categorization Of Meat Productsmentioning
confidence: 95%